SIMONE DE BEAUVOIR’S EXISTENTIALIST FEMINISM - Pavlovska, Olena; Shkil, Liudmyla (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. Simone de Beauvoir is a French writer of the XX century and the main ideologue of the feminist movement. Since the middle of the last century, her philosophical ideas have become widespread throughout Europe. However, they have never lost their relevance, and today they call for rereading and rethinking. The aim and tasks are the analysis of Simone de Beauvoir’s philosophical views as existentialist feminism based on the study of philosophical research literature on the legacy of the writer. Research methodology. The biographical, classifications, analytical methods, and the method of induction are used in the article to solve the set tasks. The research literature on the legacy of S. de Beauvoir can be divided into four parts: 1) biographical books; 2) analysis of the philosophical essay "The Second Sex"; 3) philosophical, sociological, and political science research; 4) literary analysis of the writer’s creative path. Research results. The article examines the philosophical views of the famous writer Simone de Beauvoir as existentialist feminism. The author's contribution to the development of "femininity" is a discovery of the phenomenon of Other, its definition as a certain psychological complex of inferiority, and an attempt to point the way to the possible further self-realization of women. The writer’s interpretation of history in the light of existential philosophy is revealed, where a woman is studied by the author as an existent through an artistic image, the leading meaning of which is the desire for creative and personal self-realization. It is substantiated that it is in this statement that the basic meaning of the concept of existentialist feminism of Simone de Beauvoir is revealed. Discussion. Some of the judgments of S. de Beauvoir seem to be controversial. For example, the definition of motherhood, jealousy of the mother toward an adult daughter, and others. Conclusions. It is safe to say that, firstly, Simone de Beauvoir, with her writing and philosophical work, analyzed in detail and significantly influenced the course of masculine and feminine thinking. Secondly, she revealed the need for women to realize their creative potential, i.e. to go beyond the traditional boundaries of the functions of mother and mistress, because a woman cannot and should not limit herself to these roles. Thirdly, she also credits the postulate of overcoming the Other as a psychological inferiority complex in women, which aims to discover transcendence, not immanence, activity, not passivity, strength, not weakness.